Revitalization of Local Wisdom in Balinese Short Story: an Anthropological Study - I Ketut Ngurah Sulibra; I Wayan Suteja; I Nyoman Duana Sutika (Udayana Journal of Social Sciences and Humanities, 2017)
This research was motivated by the importance of revitalizing the local wisdom of Bali for the strengthening the Bali cultural identity in order to sustain Balinese culture and national values that characterize the culture of Bali. Bali as a major tourist destination has experienced a variety of physical and non-physical problems. Therefore, the revitalization of the values of local wisdom especially in short stories that use Balinese language becomes important to be redeveloped in order to strengthen the personal and culture of Bali. The literary work is an impersonation (utnaturapoeisis), imitation or imitationaturae. In relation to the cultural values, local wisdom is a fastener segment of the various forms of culture that already existed since a long time ago, the functions as a filter, anticipatory, transformative against elements of foreign cultures. Methodologically, the data was collected by direct observation, classification, and translation that assisted with note taking and reading techniques. The collected data was analytically interpretive and descriptive analyzed. The results were presented by an informal method with deductive-inductive techniques. Based on the classification, there were four short stories analyzed. The results showed that the Balinese stories were dominated by the topic of education, the importance of self-control on drugs; hedonic behavior is a bad portrait for teenagers.